Antipsychotic exposure is an independent risk factor for breast cancer: A systematic review of epidemiological evidence - Gao, Zheng; Xi, Yin; Shi, Hekai; Ni, Jiyuan; Xu, Wei; Zhang, Kaili (Frontiers in Oncology, 2022)
BACKGROUND: The effect of antipsychotics on breast cancer remains controversial. MATERIALS AND METHODS: Embase, Scopus, PubMed, Web of Science, Cochrane Library, and Hebei Medical University Library were used for the literature search. Observational studies with original data for the effects of antipsychotics on breast cancer were used. Studies of bed quality, those with inadequate sample size, incomplete follow-up works, or studies that did not meet the criteria were excluded. Meta-analysis was performed using R version 4.1.2. The odds ratio (OR) and its 95% confidence interval (CI) were used to evaluate the proportion of breast cancer in different groups. To detect possible sources of heterogeneity, subgroup and meta-regression analyses were employed. RESULTS: Pooled data from 11 relevant studies with 1,499,001 participants suggested that individuals exposed to antipsychotics were more likely to suffer from breast cancer than those who were not exposed (OR, 1.23; 95% CI, 1.04–1.47). No significant difference in breast cancer prevalence between the atypical and typical antipsychotic groups was found (OR, 1.23; 95% CI, 0.93–1.63). Prolactin (PRL)-increasing and PRL-sparing antipsychotics posed a similar risk of breast cancer (OR, 1.13; 95% CI, approximately 0.97–1.31). Furthermore, the use of antipsychotics is attributed to increased mortality in patients with breast cancer (OR, 1.54; 95% CI, 1.29–1.82). Those exposed to antipsychotics at the maximum dose were more likely to suffer from breast cancer than those exposed to the minimum dose. CONCLUSIONS: Antipsychotic exposure is an independent risk factor for breast cancer. No significant difference in the risk of breast cancer between typical and atypical antipsychotics was noted. Those exposed to antipsychotics at higher doses are more likely to suffer from breast cancer. Moreover, the use of antipsychotics is attributed to increased mortality in patients with breast cancer. PRL-increasing and PRL-sparing antipsychotics pose a similar risk of breast cancer.